ANESTEZJOLOGIA I INTENSYWNA TERAPIAGeneral anaesthesia with remifentanil or fentanyl for elderly patients during thoracoscopic procedures - Misiołek, Hanna; Budziński, Dariusz; Przybyła, Maciej; Wojtacha, Anna; Filipowski, Marek; Karpe, Jacek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Background: Non-invasive procedures including thoracoscopies cause less operative trauma and stress and in the postoperative period fewer pain ailments, which results in a shorter hospitalization period and decrease of treatment costs. The operative technique that requires one lung ventilation and lateral decubitus position leads to a series of ventilatory and cardiovascular disturbances. The anaesthesia risk is elevated, especially in elderly patients. Aim: To determine whether the use of opioids with different duration of action (remifentanil or fentanyl) influences the cardi-ovascular system response to one lung ventilation in elderly patients. Material and methods: The study had a prospective and randomized design. In the test group I (n = 19) for the analgesia remifentanil 0.5 µg kg-1 (bolus) and then continuous infusion of 0.05-0.1 µg kg-1 was used. In the control group II (n = 21) for the analgesia fentanyl in standard doses was used. For direct blood pressure and cardiac output monitoring a special artery sensor (FloTrac) was used. The values of the following parameters were specified: HR, SBP, DBP, MBP, SV, CI, SVR. Results: The values of haemodynamic parameters measured during the study were comparable in both groups. Conclusion: The use of different action time opioids does not influence the cardiovascular system reaction during one lung ventilation in elderly patients.